2021
DOI: 10.15376/biores.16.4.8289-8308
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for and adoption of Industry 4.0 among small and medium sized enterprises in the Malaysian furniture industry

Abstract: The furniture industry is the fastest growing sub-sector in the Malaysian wood-based industry. Although it has grown tremendously over the years, it is characterized by stagnating value-addition. To improve industrial competitiveness, automation and technology application has emerged as a possible solution. A study was conducted to evaluate the influence of company size towards their readiness and adoptability of automation and Industry 4.0. A questionnaire-based survey involving large-, medium-, small-, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Nevertheless, as with the adoption of Industrial Revolution 4.0 technologies (Yi et al 2021), the adoption of ESG practices must also be facilitated by the relevant government agencies, especially the Malaysian Timber Industry Board (MTIB) and the Malaysian Timber Council (MTC), through awareness and readiness assessment programs. Financial support in the form of cost-subsidies and grants should also be made available for enterprises, especially the SMEs, to prepare themselves for the adoption of ESG practices.…”
Section: Recommendations To Policymakersmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as with the adoption of Industrial Revolution 4.0 technologies (Yi et al 2021), the adoption of ESG practices must also be facilitated by the relevant government agencies, especially the Malaysian Timber Industry Board (MTIB) and the Malaysian Timber Council (MTC), through awareness and readiness assessment programs. Financial support in the form of cost-subsidies and grants should also be made available for enterprises, especially the SMEs, to prepare themselves for the adoption of ESG practices.…”
Section: Recommendations To Policymakersmentioning
confidence: 99%
“…"Furniture ESG practices," BioResources 18(1), 1436-1453. 1438 Yi et al 2021) have also reported that the size of the company also influences its decision to invest in technology, sustainable practices, and modern manufacturing systems. Therefore, it is clear that the size of the company in the wood products and furniture industries plays an important role in its ability to transform and comply with new market requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The Malaysian furniture industry, which is fundamental to strengthening the Malaysian brand and fashion sector has proven to be a significant economic force in the competitive global market. The year 2019 was a milestone of growth, with the domestic market reaching RM8.9 billion (MTIB, 2020) and furniture exports have escalated to RM10.52 million, with wood-based products contributing RM22.1 million, representing a significant 83% of the country's total export, thereby reinforcing Malaysia's status as a leading furniture exporter with a substantial portion of its production reaching over 160 countries worldwide (Yusof et al, 2023;Yi et al, 2021). This success is largely dependent on the contributions of SMEs, which boost GDP, encourage entrepreneurial ventures, and employ approximately 105, 000 people (MTIB, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the transformation is fraught with challenges, mainly due to the financial constraints and other systemic challenges faced by SMEs that hinder their ability to drive innovation at both individual and organizational levels (Ratnasingam et al, 2021). Yi et al, (2021); and Abu and Mansor (2019) describe these issues, as nothing that these financial barriers hinder the recruitment or development of skilled workers, thwart Industry 4.0 adoption efforts, and limit engagement in innovation practices. Ratnasingam et al, (2020) reinforce this perspective, by detailing how systemic challenges, such as policy volatility and inconsistencies in the supply of raw materials, further exacerbate the situation.…”
Section: Introductionmentioning
confidence: 99%